2015
DOI: 10.2147/ijn.s79892
|View full text |Cite
|
Sign up to set email alerts
|

Application of dental nanomaterials: potential toxicity to the central nervous system

Abstract: Nanomaterials are defined as materials with one or more external dimensions with a size of 1–100 nm. Such materials possess typical nanostructure-dependent properties (eg, chemical, biological, optical, mechanical, and magnetic), which may differ greatly from the properties of their bulk counterparts. In recent years, nanomaterials have been widely used in the production of dental materials, particularly in light polymerization composite resins and bonding systems, coating materials for dental implants, biocer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 151 publications
0
8
0
Order By: Relevance
“…This study investigates issues related to the antibacterial activities of zinc oxide and silver nanoparticles against the bacteria responsible for odontogenic infections in the area of the head and neck, as well as their behaviour in the saliva. The release of H 2 O 2 is a possible mechanism for the antibacterial activity of ZnO NPs,69 whereas the antibacterial activity of Ag NPs is based on cell lysis through the inhibition of DNA replication, expression of ribosomal and cellular proteins and interference with the electron transport chain 70…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigates issues related to the antibacterial activities of zinc oxide and silver nanoparticles against the bacteria responsible for odontogenic infections in the area of the head and neck, as well as their behaviour in the saliva. The release of H 2 O 2 is a possible mechanism for the antibacterial activity of ZnO NPs,69 whereas the antibacterial activity of Ag NPs is based on cell lysis through the inhibition of DNA replication, expression of ribosomal and cellular proteins and interference with the electron transport chain 70…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they showed that zinc oxide NPs were significantly more effective against S. mutans than nanosilver. According to another study, Salem et al,70 zinc oxide nanoparticles inhibit adenylyl cyclase activity leading to the decade of the second messenger in the process of biofilm formation. In this study, biofilm formation was not evaluated, but the zinc oxide nanoparticles used as the sole antibacterial agent were significantly inferior to hydrosilver, which confirmed other observations that Zn NPs exhibited a relatively low antibacterial capacity 72,73.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TiO 2 nanoparticles (TiO 2 -NPs) and ZnO nanoparticles (ZnO-NPs) are used in 43 and 25 different categories of cosmetics, respectively [ 5 ]. Biomedical applications in imaging diagnostics, such as drug carriers or dental composite resins, together with applications in food industry packaging or as taste carriers or sensors [ 2 , 6 , 7 ], are matters of serious concern about human exposure. Moreover, the Organization for Economic Cooperation and Development (OECD) has included TiO 2 -NPs and ZnO-NPs among those NMs whose safety should be addressed as a priority [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when mechanical stress overwhelms components’ protective capacity, corrosive substances such as metallic particles, inorganic metallic salts as well as free metal ions are released. 43 These products, mostly released from metal-on-metal (MOM) and metal-on-polyethylene (MOP) bearings, can accumulate in the surrounding tissues, or even disseminate to distant lymph nodes and organs, 44 – 46 causing adverse local and/or systemic risk.…”
Section: Metal Npsmentioning
confidence: 99%